Women Who Stay Behind Pedagogies of Survival in Rural Transmigrant Mexico - Trinidad Galván, Ruth (University of Arizona Press, 2015)
Women Who Stay Behind examines the social, educational, and cultural resources rural Mexican women employ to creatively survive the conditions created by the migration of loved ones. Using narrative, research, and theory, Ruth Trinidad Galván presents a hopeful picture of what is traditionally viewed as the abject circumstances of poor and working-class people in Mexico who are forced to migrate to survive.